Correlation between the time elapsed after liposuction and the risk of fat embolism: An animal model - Kwang-Ryeol Lim; Jeong-Min Cho; Chung-Min Yoon; Keun-Cheol Lee; Sang-Yun Lee; Mi-Ha Ju (Archives of Plastic Surgery, 2018)
Background Liposuction has become one of the most frequently performed procedures in the field of aesthetic surgery. Fat embolism syndrome after liposuction can easily be overlooked or underestimated; however, occasionally, fulminating fat embolism syndrome can develop and lead to a critical situation within 2–3 days after lipoplasty. Changes over time in the amount of circulating fat particles and the histology of major organs have not yet been studied.